Marketing Strategy for Processed Coffee at Kahayya II Farmer Group in Kindang District, Bulukumba Regency - Pundising, Rudy Immanuel; Ramli, Ramli; Sukarsih, Sri Endang; Junaidi, Junaidi; Ramadhani, Andi Nurul Amalia; Samaria, Samaria (Program Studi Agribisnis Universitas Muhammadiyah Sinjai, 2024)
Coffee has a vital role in Indonesia's economic activities. Kahayya coffee is an ancestral heritage from the wilderness of Kahayya Village. In several lines of coffee production centers, farmers and farmer groups in Kahayya sell raw coffee and generally sell their production to intermediary traders at relatively low prices. This is one of the reasons why the price obtained could be more optimal. Also, farmers consider it an advantage because their agricultural products are quickly sold and do not need to incur costs for the distribution process, namely transportation to the market. The results showed that Kahayya Coffee Marketing still needs to be optimal; many farmers still sell at low prices due to the limited ability of farmers to analyze competitor price information. The strategy is to conduct a market survey by visiting Kahayya Coffee's salesplaces, such as coffee shops or other cafes. The purpose of conducting this research is also to find out the price sold in the market, whether it shows profit or even harms farmers. One of the strategies is the existence of a cafe in Kahayya. Nature tourism facilitates farmers' marketing because when visitors go to Kahayya, they can enjoy Kahayya coffee while enjoying the tourist attractions in Kahayya.